Implementasi Penerapan Restorative Justice Dalam Manajemen Penanganan Kecelakaan Lalu Lintas : di Wilayah Hukum Polres Tangerang Selatan - Alvan Fauzan; Ilham Prisgunanto (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the application of restorative justice through mediation in handling traffic accident cases by the police. This research uses several theoretical foundations, namely restorative justice theory which emphasizes the restoration of the relationship between perpetrator and victim, communication theory which explains the process of message delivery and interaction between the parties involved in mediation, and non-penal mediation theory which focuses on resolving cases outside the criminal justice process through deliberation and mutual agreement. The research method used is a qualitative method with an analytical descriptive approach. Data collection was carried out through interviews, observations, and documentation with informants consisting of the Chief of Police, Head of Police, Kanit Gakkum, investigator members, and the public who had been involved in the settlement of traffic accident cases. The results of the study show that the application of restorative justice in handling traffic accident cases has been carried out by prioritizing the interests of victims, the responsibility of the perpetrators, and the restoration of social relations in the community. The mediation process facilitated by the police provides a space for dialogue for the parties to reach a fair and mutually acceptable agreement.